"Teori Ancaman China" dan Hubungan Ekonomi Malaysia-China (Journal of International Studies, 2020)
Since the introduction of the 'Four Modernizations' in China by Deng Xiaopeng in 1978. China s economy has experienced tremendous development especially when it became an attractive destination for Foreign Direct Investment (FDI). This development has changed the status of China from the 'backward' image of a Communist country to a new economic dynamo of growth in the region. Infacing this situation, it is inevitable for Malaysia to deny China s economic expansion. As such, Malaysia has tried to improve its ties with China to ensure that it will share China's economic prosperity. Instead, Malaysia sees China as an opportunity rather than a threat to its economy. This article contends that Malaysia-China economic relations are becoming more important and have a bright prospect to develop in the near future. Although there are issues that at times challenged their relationship, Malaysian leaders ignored the problems and continue to improve their economic ties.